Album of photographs of Sydney Harbour and other views - Kerry & Co. (1883)
Views of ships, the harbour, yachts (dated ca. 1935), the Garden Palace, the Free Public Library, the unveiling of the statue of John Dunmore Lang in Wynyard Square in 1883. Some of the photographs have embossed stamp Kerry & Co.
Keywords: Sydney (N.S.W.) -- Pictorial works